Implementation of an analytical microfluidic device for the quantification of protein concentrations in high-throughput format - Radtke, Carsten Philipp; Schermeyer, Marie-Therese; Zhai, Yün Claudia; Göpper, Jacqueline; Hubbuch, Jürgen (Engineering in life sciences, 2016)
Nowadays, the performance of experiments in automated microliter scale format is common practice in the biopharmaceutical process development. The increased number of experiments, reduced sample volumes, and usage of robotic platforms require the adjustment of photometric measurements to determine the protein concentration. This work presents the qualification and usage of a disposable measurement device that can be used with conventional microplate photometers. The application of the microfluidic device (μF‐device) allows absorption measurements of protein concentrations from around 0.1 to 100 mg/mL with an accuracy of 99.2% dependent on given protein extinction coefficients. The integrated four measurement chambers of increasing height (100–1500 μm) allow the direct calculation of calibration curves and the determination of protein concentrations independent of used optical path lengths with a sample volume of 36 μL. This study contains the validation of the analytical μF‐device according to ICH Guidelines as well as a representative case study. A salt gradient screening with chromatography columns in microliter scale performed on a liquid handling station presents the usability of the μF‐device. It is shown that an improvement of the repeatability and accuracy of the chromatograms could be achieved by μF‐device implementation in comparison to photometric measurements performed in microtiter plates.